The teachers’ awareness and utilisation of innovative strategies for teaching and learning in Awka South - Christian-Ike, Nwanneka Oluchukwu; Nnalue, Obioma Henrietta; Nwuba, Izunna Shedrack (Inornatus: Biology Education Journal, 2024)
Basic science's role in instilling a love of science and laying the groundwork for science studies in senior secondary school prompted the survey of teachers' awareness and utilization of innovative teaching strategies for effective teaching and learning of basic science in upper basic education. The study adopted a survey research design. The population comprised all the 36 basic science teachers in the 19 public secondary schools in Awka South local government area. Questionnaire was used to collect data. Data was analyzed using descriptive statistics of frequency and mean scores. The study found that the teachers are aware of majority of innovative teaching strategies for teaching Basic science. The extent basic science teachers use innovative teaching strategies in enhancing basic science teaching in upper basic education was to a low extent. The study concluded that the basic science teachers are aware of the majority of innovative teaching strategies but their application within the classroom remains low. This discrepancy between awareness and practice highlights a critical gap in the implementation of effective pedagogical approaches for basic science education. The study recommended that the government through her relevant educational agencies should design and implement comprehensive training programs focused on equipping teachers with the necessary skills and knowledge to effectively utilize various innovative teaching strategies in the basic science classroom.